Main nursing diagnoses in hospitalized elderly people who underwent urological surgery - Walisson Guimarães Lima; Simony Fabíola Lopes Nunes; Angela Maria Alvarez; Rafaela Vivian Valcarenghi; Maria Luiza Rêgo Bezerra (Rev Rene)
Objective: to identify the main nursing diagnoses in the elderly during postoperative period of urologic surgeries. Methods: Cross-sectional and quantitative study conducted in a urological unit. Data collection was conducted through physical examinations and consultation to medical records. One hundred senior citizens who were hospitalized at the institution participated in the study. Results: The most frequent urological surgical procedures were: transurethral resection of the prostate (27 %) and open prostatectomy (16 %). Among the nursing diagnoses identified, impaired skin integrity (100 %), risk of infection (100 %), Risk for deficient fluid volume (84 %) acute pain (68 %) and deficient knowledge (61 %) had a higher number of occurrences. Conclusion: the findings allowed, through nursing diagnoses, nursing interventions in the postoperative period of urological surgeries, providing the implementation of effective and immediate actions to solve problems.